KODE ETIK ADVOKAT SEBAGAI DASAR ITIKAD BAIK ADVOKAT DALAM MENJALANKAN PROFESINYA TIDAK DITUNTUT PERDATA MAUPUN PIDANA - Tumbur Ompu Sunggu; Tajuddin (Law Department, University of Widya Gama Mahakam Samarinda, 2023)
The advocate's code of ethics is the cornerstone of advocates in carrying out their professional duties in defending the interests of clients inside and outside the courtroom in good faith, because the advocate's code of ethics governs all behavior of advocates in carrying out their professional duties in providing legal assistance and defense by upholding the law and legislation. Invitation in accordance with the oath of office. The author uses the normative legal research method (normative juridical). Advocates are an honorable profession (officium nobile), namely advocates in carrying out and carrying out their professional duties to defend the interests of their clients' legal rights are protected by law and law as well as the Advocate Code of Ethics. In carrying out their professional duties, advocates also have the freedom to adhere to independence, honesty, confidentiality and openness. Where the legal position of the advocate profession is as one of the law enforcers whose position is equal to other law enforcement agencies, so that one another must respect each other between colleagues and other law enforcers. Because Advocates are an honorable profession (officium nobile), Advocates must maintain their honor in front of the public by adhering to the advocate's code of ethics, as a basis of good faith not to be prosecuted civil or criminal.